Effect of pulsed electric field on assembly structure of α-amylase and pectin electrostatic complexes. (April 2020) - Jin, Weiping; Wang, Zhifeng; Peng, Dengfeng; Shen, Wangyang; Zhu, Zhenzhou; Cheng, Shuiyuan; Li, Bin; Huang, Qingrong
Abstract: Pulsed electric field (PEF) could change the charge distribution of proteins and polysaccharides and affect their interactions and complexes aggregation, but those influences are not enough evaluated. Here, the effects of PEF on the complexes of α-amylase and pectin driven by electrostatic binding were studied. Changes in molecular conformation of α-amylase and assembly structure of α-amylase/pectin complexes were orderly assessed by fluorescence, FTIR, DSC, enzyme activities, particle size, ζ-potential, CLSM, and SEM. After PEF treatment ( E ~20 kV/cm, texp ~1 ms, and 5 cycles), the intrinsic fluorescence of α-amylase was quenched, the content of β-sheet increased, enzyme activities lose almost 80%, and the denatured temperature increased. Ζeta-potential of α-amylase/pectin complexes did not change significantly, but the particle size rose gradually. The particle revolution of α-amylase/pectin complexes was recorded by Turbiscan, and the size growth model fit the Allometric function well. Finally, the complexes of α-amylase and pectin after PEF treatment tended to the branched, ring, or circles-like shape. Graphical abstract: Assembling behavior of alpha-amylase and pectin complexes after pulsed electric field treatment. Image 1 Highlights: Electrostatic binding of α-amylase to pectin increased the enzyme sensitivity to PEF. Zeta potential of α-amylase/pectin complexes did not change significantly after PEF treatment. Particle size of α-amylase/pectin complexes rose gradually after PEF treatment. Final structure of complexes after PEF treatment showed the branched, ring, or circles-like shape.